COVID-19: Regulation of Migration Processes in The European Legal Area - Kortukova, Tamara O.; Dei, Maryna O.; Blahodarnyi, Andrii M.; Kaminska, Natalіya V. (Cuestiones Políticas, 2020)
The rapid spread of the virus around the globe, the widespread introduction of restrictions on freedom of movement and declarations by governments about the great threat to public health on a global scale, have had a serious impact on migration processes in the world. The European legal space has some regulation of migration processes, developed within the framework of the EU, the Council of Europe and the OSCE. However, COVID-19 presented him with some additional challenges. The purpose of the article is to analyze the legal regulation of migration processes within the European legal area in the conditions of the COVID-19 pandemic. The main method to study this problem is the comparative analysis, which allows to compare the legal regulation of migration processes during COVID-19 in three organizations: the European Union, the Council of Europe and the OSCE. In conclusion, the pandemic once again demonstrated the tendencies of national isolation, which exist in the European continent. The EU closes internal borders, the members of the Council of Europe make an exception to the rights contained in the European Convention on Human Rights, but they do not notify the Secretary General of the Council of Europe.